Self-Disclosure and Respect: Understanding the Engagement of Value Minorities - Dumas, Tracy L.; Doyle, Sarah P.; Lount, Robert B. (Organization Science, 2024)
Organizations benefit from including employees with dissimilar values and perspectives, but their ability to realize these benefits is constrained by the degree to which those holding the dissimilar values (i.e., value minorities) feel comfortable engaging with their colleagues and the work of the collective. We extend theory on value dissimilarity by directly examining the experience of individuals whose values are dissimilar from those of their colleagues, and factors driving their engagement in work. Our examination spanned three studies: a laboratory experiment, a vignette study of employed adults, and a three-wave survey of student project groups. We found that the negative relationship between holding dissimilar values from one’s colleagues and engagement was lessened when value minorities disclosed personal information unrelated to their dissimilar values (Studies 1–3). Self-disclosure also moderated the negative relationship between value dissimilarity and feeling respected by one’s colleagues (Studies 2 and 3). Furthermore, felt respect mediated the effect of value dissimilarity on engagement, and this indirect effect was moderated by self-disclosure (Studies 2 and 3). Overall, this research is relevant to organizations seeking to capitalize upon the benefits of minority perspectives in the workforce but suggests that a critical first step is to prioritize the experience of value minorities and the decreased sense of social worth that can accompany this experience. By fostering an environment conducive to self-disclosure, organizations can help to alleviate the discomfort associated with value dissimilarity, thereby ensuring that all people, including the value minority, feel respected and are maximally engaged at work. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2021.15768 .